3D modelling of large urban scenes from diverse sources of information - António Fernando Coelho (2003)
The complex and extensive nature of urban environments creates difficulties to the task of generating virtual models. Thus a great effort in terms of human resources, time and money is needed. Nevertheless a large number of professionals and institutions devout efforts to gather and analyse data from these urban environments. As data is usually stored in a digital format, it becomes a valuable asset to incorporate it in the modelling process of virtual environments. This paper presents a three-dimensional modelling system with interoperable access to data in diverse formats and digital support, drived by an L-system based modelling process that automatically generates initial solutions for virtual environments, which can be incrementally improved.